Quick response manufacturing (QRM) uma alternativa para redução do lead time na área produtiva de uma empresa de materiais de escrita - Saes, Elizangela Veloso (2010)
The approach Quick Response Manufacturing (QRM) has been proposed in the late ninety, and since then, has been successfully deployed in many companies, achieving promising results in reduction of lead time in environments with high product variety. This approach, although already established abroad, mainly in the United States, is poorly known in Brazil as not to have official records of its practice, thus providing a vast new area of research. From this context that this dissertation aims to explore and understand the general ways to reduce lead time based on QRM and propose a practical application of this approach. For this objective to be achieved, we sought, first, the comprehensive review of the literature concerning the reduction of lead time, describing the tools and principles to reduce lead time in the QRM approach and then propose to implement some of the principles and tools of QRM in the production area in a business of writing. This proposed implementation of QRM is analyzed and validated by simulations that visualize the interactions of variables from the factory floor and the effects of these variables in the percentage of use of sectors in the intermediate level of inventory (WIP) and lead time. It is hoped that the practical implementation of the proposals to reach a 55% reduction from the current level of WIP company and up to 77% in the average lead time of its products. Thus, this research contributes to the theory and practice in management of manufacturing systems, showing the importance of reducing lead time and the effects and benefits of implementing QRM in a Brazilian company.